2022
DOI: 10.3389/fpsyg.2022.1019976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of media use, smart phone addiction, and adult ADHD symptoms on wellbeing of college students during the COVID-19 lockdown: Dispositional hope as a protective factor

Abstract: IntroductionThe present study investigated the role of dispositional hope as a potential protective factor moderator in the relationship between adult ADHD symptoms, media use/smart phone addiction and wellbeing during the period of isolation because of the COVID-19 pandemic among students in Romania.MethodsA sample of 333 college students (86.8% female and 13.2% male) between the age of 18 and 47 with a mean of 20.6 years old from West University of Timişoara completed online surveys. Mediation and moderation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Sense of hope significantly and positively predicted secondary school students’ psychological resilience and mental health, and a further mediating effect test revealed that psychological resilience plays a mediating role between the sense of hope and mental health. Based on hope theory, as a positive personal trait, sense of hope promotes secondary school students to think positively about more possibilities when they face adversities and stressful events ( Toma et al, 2022 ), inspires them to keep accumulating knowledge and experience that are conducive to achieving their goals, and at the same time helps them to strengthen their confidence in overcoming difficulties and build up their expectations for a better future ( Geiger et al, 2021 ). High hope traits help secondary school students to expand the cognitive scope, develop positive self-assessment and responses ( Ling et al, 2020 ), and provide secondary school students with additional psychological resources that further contribute to their psychological resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Sense of hope significantly and positively predicted secondary school students’ psychological resilience and mental health, and a further mediating effect test revealed that psychological resilience plays a mediating role between the sense of hope and mental health. Based on hope theory, as a positive personal trait, sense of hope promotes secondary school students to think positively about more possibilities when they face adversities and stressful events ( Toma et al, 2022 ), inspires them to keep accumulating knowledge and experience that are conducive to achieving their goals, and at the same time helps them to strengthen their confidence in overcoming difficulties and build up their expectations for a better future ( Geiger et al, 2021 ). High hope traits help secondary school students to expand the cognitive scope, develop positive self-assessment and responses ( Ling et al, 2020 ), and provide secondary school students with additional psychological resources that further contribute to their psychological resilience.…”
Section: Discussionmentioning
confidence: 99%